Relationship between Geomagnetic Indices (Kp, Ap) and Solar Activity (Sunspot Number) - Samanta, Debasri; Dolai, Rajib Kumar (Api Journal of Science, 2025)
This study examines the relationship between solar activity (Sunspot Number) (SSN) and geomagnetic indices (Kp and Ap) using time-series decomposition, distribution analysis, and correlation analysis. The results show an inverse relationship between Kp, Ap, and SSN up to 1990, followed by a strong positive correlation thereafter. Distribution analysis indicates that SSN is dominated by low-frequency components, whereas Kp and Ap capture both long-term trends and shorter-term variations, such as the ~ 27-day solar rotation cycle. Correlation analysis reveals weak overall correlations but strong trend correlations, particularly during the 12:00–15:00 UT interval for Kp and Ap with SSN.